2022
DOI: 10.3390/molecules27051497
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Impedance Spectroscopy in the Characterisation and Application of Modified Electrodes for Electrochemical Sensors and Biosensors

Abstract: Electrochemical impedance spectroscopy is finding increasing use in electrochemical sensors and biosensors, both in their characterisation, including during successive phases of sensor construction, and in application as a quantitative determination technique. Much of the published work continues to make little use of all the information that can be furnished by full physical modelling and analysis of the impedance spectra, and thus does not throw more than a superficial light on the processes occurring. Analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(67 citation statements)
references
References 36 publications
(45 reference statements)
2
44
0
1
Order By: Relevance
“…The easiest circuit able to fit the EIS experimental data is reported in the inset of Figure 6 a. The latter is an adapted form of the Debye circuit which results from the parallel of an ionic resistance (R1) in series with a double layer capacitance (Q1) at the electrode surface and a dielectric capacitance (C1) [ 75 , 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…The easiest circuit able to fit the EIS experimental data is reported in the inset of Figure 6 a. The latter is an adapted form of the Debye circuit which results from the parallel of an ionic resistance (R1) in series with a double layer capacitance (Q1) at the electrode surface and a dielectric capacitance (C1) [ 75 , 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…Electrochemical impedance spectroscopy (EIS) is one of the most important electrochemical techniques for interrogating surface chemistries which can be applied to detecting interfacial binding events through impedance measurements (in ohms). EIS has advantages over other electrochemical methods, such as that it is a steady-state technique, uses small signal analysis, and that it can investigate signal relaxation over a very wide range of applied frequencies with commercial usage [ 44 , 45 ]. On the other hand, EIS can be applied for assessing the electrical characteristics of nanomaterials, detecting and investigating the behavior of the electrode surface by delivering a sinusoidal voltage across a wide frequency range, and measuring the current with the least negative impact [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…In order to deepen the topic, several particularly meaningful reviews are suggested, including interesting examples of impedimetric biosensors [ 31 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Electrochemical Biosensorsmentioning
confidence: 99%